Moral virtue and contemplation : a note on the unity of the moral life - Gallagher, David M. (Sapientia, 1996)
The notion of contemplation as the goal of life is, it seems, as old as philosophy itself. Already Anaxagoras, when asked why he was in the world, replied, «To contemplate » (eis theorian)'. So too, both Plato and Aristotle placed man's highest fulfillment in contemplative activity, that activity which, more than any other, shared in the divine. No less did Thomas Aquinas —within the Christian tradition— accept that view, adding to the philosophical the evangelical dictum that Mary had chosen the better part. And yet, both philosophers as well as Christians also pointed to moral action as essential to a fulfilled human life, as being in some way the goal of our lives. Socrate's urging to the philosophical life in no way lessened his demand for justice; Aristotle postulated a secondary happiness, one based on the moral virtues; and Aquinas, while placing man's end in contemplation, also points to the rectitude of the will as its necessary prerequisite. It is this relationship of the moral life —understood as the activities of the moral virtues— to contemplation that forms the theme of this article. In the context of St. Thomas, I wish briefly to examine 1) how the moral life points to a human fulfillment beyond itself; 2) in what way the moral virtues remove certain obstacles to contemplation; and finally, 3) in what way the moral virtues provide the rectitude of the will required for the contemplative life.